Towards an operational framework for designing training based sports virtual reality performance simulators - Shepherd, J.; Carter, L.; Pepping, G.-J.; Potter, L.-E. (Proceedings, 2018)
With the advent of commercially available virtual reality (VR) hardware, immersive experiences can be created to simulate competitive performance environments. Simulators can provide novel ways for fans to engage with otherwise unattainable performance situations. Furthermore, simulators can also have clear advantages for elite athletic training by controlling the perceptual inputs, measuring the kinematic based outputs, measuring how the athlete is interacting with the created environment, and providing concurrent audio-visual-haptic feedback. When engineering a virtual simulation system, fundamental design considerations include; hardware selection, software design, user safety, and the provision of performance factors. This paper provides a case study into the design considerations of engineering a track cycling simulator for the 2018 Commonwealth Games Velodrome. The experience utilises a stationary exercise bike (Wattbike, 2016 Pro) transmitting performance data wirelessly, via the ANT+ protocol, to a PC connected to an Oculus Rift VR projecting the audio-visual simulated environment. The simulator has been tested on a large reference group to evidence the design decisions. The design processes have been generalized to create an operational framework to aid the creation of future VR sports simulators.